PENGEMBANGAN INSTRUMEN PENILAIAN KESIAPAN ORGANISASI KEARSIPAN DALAM MENANGGULANGI BENCANA DI DEPO ARSIP KOTA BATU - Moch. Alfa Alfiansyah; Moh. Safii (Program Studi Diploma Tiga Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2024)
Archives are important assets for an organization, yet their management is often suboptimal, including a lack of attention to archival disaster management, especially for archival organizations lacking readiness measurement tools for disaster preparedness. The aim of this development is to create an assessment instrument for evaluating archival organizations' readiness in disaster management that can be universally applicable. This instrument can be reviewed in terms of content, language, and technical aspects structured based on indicators outlined in the National Archives of Indonesia's Standard Procedures and Criteria Guideline for Archive Protection and Rescue from Disasters 2013. The development model used is the Borg and Gall model with quantitative data obtained from a validation questionnaire. The outcome of this development is a produced product, namely the